Changes in cooked ham inoculated with lactic acid bacteria - Belichovska Daniela, Pejkovski Zlatko, Belichovska Katerina (Faculty of Agricultural Sciences and Food, University Ss. Cyril and Methodius in Skopje, 2015)
Changes in pH, production of metabolites (glucose, lactic acid, ethanol) and sensory properties during storage of cooked ham inoculated with lactic acid bacteria Leuconostoc citreum, Lactobacillus sakei and Weisella viridescens were investigated. It was found that pH of the ham was almost identical in each strain of used bacteria up to the 30th day of the experiment and varied from 6.01 to 6.09. A major change in pH value was not observed in Leuconostoc citreum. Lactobacillus sakei had a normal pH up to the 30th day, and then started to decline rapidly, while in Weisella viridescens rapidly declined after the 40th day. At the beginning, the concentration of glucose was the same (1 g/kg) in all strains of bacteria, it was reduced at the end, and, in some species, it was almost not present. Concentration of lactic acid in all strains of bacteria was very similar at the beginning and then started to grow slightly. At the moment when reached the highest level, then pH began to decline. Ethanol was found in higher concentrations at the end of the experiment.
Keywords: cooked ham, changes during storage